Cost analysis of insulin degludec in comparison with insulin detemir in treatment of children and adolescents with type 1 diabetes in the UK - Thalange, Nandu (BMJ Open Diabetes Res Care, 2019)
OBJECTIVE: With healthcare systems under increasing financial pressure from costs associated with diabetes care, it is important to assess which treatments provide clinical benefits and represent best value. This study evaluated the annual costs of insulin degludec (degludec) versus insulin detemir (IDet) in children and adolescents with type 1 diabetes (T1D) in the UK. RESEARCH DESIGN AND METHODS: Using data from a randomized, treat-to-target, non-inferiority trial—BEGIN YOUNG 1—annual costs with degludec versus IDet in children and adolescents aged 1–17 years with T1D were estimated, as costs of these insulins and hyperglycemia with ketosis events. Analyses by age group (1–5, 6–11 and 12–17 years) and scenario (no ketosis benefit, no dose benefit, hyperglycemia with ketones >0.6 and >3.0 mmol/L and the additional costs of twice-daily IDet in 64% of patients) were also performed. RESULTS: The mean annual cost per patient was estimated as £235.16 for degludec vs £382.91 for IDet, resulting in an annual saving of £147.75 per patient. These substantial cost savings were driven by relative reductions in the frequency of hyperglycemia with ketosis and basal insulin dose with degludec versus IDet. Annual savings in favor of degludec were observed across each age group (£122.63, £140.59 and £172.50 for 1–5, 6–11 and 12–17 years age groups, respectively). Five scenario analyses further demonstrated the robustness of the results, which included no ketosis or dose benefits in favor of degludec. CONCLUSIONS: Degludec provides appreciable annual cost savings compared with IDet in children and adolescents with T1D in a UK setting. While a cost-effectiveness analysis could incorporate the health impact of treatment complications better than the present cost analysis, the strong generalizability of the data from this study suggests that degludec can help healthcare providers to maximize health outcomes despite increasingly stringent budgets.